Accuracy of Sagittal Plane Component Alignment in Robotic-Assisted Total Knee Arthroplasty - Justin O. Aflatooni, MD; Austin E. Wininger, MD; Thomas C. Sullivan, BS; Timothy S. Brown, MD; Kwan J. Park, MD (Arthroplasty Today)
Background: Robotic-assisted total knee arthroplasty (rTKA) is utilized to facilitate accurate and precise resection goals. Most literature has focused on postoperative limb and component alignment in the coronal plane. This study sought to evaluate the accuracy of 2 robotic systems in executing sagittal plane resections during rTKA. Methods: This retrospective review analyzed 169 consecutive primary rTKAs at a single institution from January 2023 to January 2024. Surgeries were performed by two fellowship-trained arthroplasty surgeons, each using a different rTKA system (73 System 1 and 96 System 2). Femoral and tibial component sagittal alignment were measured on postoperative and compared to intraoperative plans. Results: Both systems more frequently resulted in reduced tibial slope than planned slope (75.3% System 1, 84.4% System 2). The average absolute difference between planned and measured tibial slope was 1.4 ± 1.0° (P = .01) for System 1 and 2.4 ± 1.5° (P < .001) for System 2 with 93.9% and 66.7% having a difference of <3°, respectively. For femoral component sagittal alignment, both systems resulted in roughly an even split of cases with increased and decreased femoral flexion. The average absolute difference between planned and measured femoral flexion was 1.5 ± 1.1° (P = .23) for System 1 and 1.8 ± 1.5° (P = .28) for System 2 with 90.4% and 86.5% having a difference of <3°, respectively. Conclusions: These findings better elucidate discrepancies between planned and executed tibial and femoral sagittal component alignment of 2 popular robotic systems, which may play an important role as TKA limb alignment and component positioning goals become more individualized.